Pedagogical and Enlightening Views of Eastern Thinkers on the Formation of Musical Culture - Dildora Abduvahobovna Djamalova (Researchparks Publishing, 2022)
This article discusses the popularization of musical culture and the role of enlighteners in the musical culture of Eastern thinkers. In addition, an analysis was made of the work carried out in Uzbekistan to form a musical culture in the minds of students.